Emerging Roles of Downstream of Kinase 3 in Cell Signaling - Loh, Jia Tong; Teo, Joey Kay Hui; Lim, Hong-Hwa; Lam, Kong-Peng (Frontiers in Immunology, 2020)
Downstream of kinase (Dok) 3 is a member of the Dok family of adaptor proteins known to regulate signaling pathways downstream of various immunoreceptors. As Dok-3 lacks intrinsic catalytic activity, it functions primarily as a molecular scaffold to facilitate the nucleation of protein complexes in a regulated manner and hence, achieve specificity in directing signaling cascades. Since its discovery, considerable progress has been made towards defining the role of Dok-3 in limiting B cell-receptor signaling. Nonetheless, Dok-3 has since been implicated in the signaling of Toll-like and C-type lectin receptors. Emerging data further demonstrate that Dok-3 can act both as an activator and inhibitor, in lymphoid and non-lymphoid cell types, suggesting Dok-3 involvement in a plethora of signal transduction pathways. In this review, we will focus on the structure and expression profile of Dok-3 and highlight its role during signal transduction in B cells, innate cells as well as in bone and lung tissues.